Implementasi Penyaluran Bantuan Sosial Kepada Korban Bencana Banjir di Kecamatan Waru Kabupaten Sidoarjo - Oktaviani, Diana; Sheila Puspaningrum; Friska Mauliva; Nabiilah Haniifah Azizah; Ertien Rining Nawangsari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to describe in more detail the distribution of social assistance (bansos) carried out by the Sidoarjo Regency Government to residents of Waru District who were affected by the flood disaster. Using qualitative research methods, this research refers to David C. Korten's Implementation Theory with three indicators, namely 1) Conformity between the program and utilization, 2) Conformity between the program and the implementing organization, and 3) Conformity between the user group and the implementing organization. This research uses a three-stage data collection technique, namely interviews, documentation, and literature study involving the Sidoarjo Regency Government, stakeholders involved, and residents of Waru District who were affected by the flood. The research results show that the distribution of social assistance for flood disasters in Waru District has operated well, with indicators 1) The suitability of the social assistance program which has been right on target, namely distributed to flood disaster victims in Waru District; 2) Suitability of the program that has been implemented by the appropriate officer according to their field; and 3) Suitability for the people of Waru District who receive social assistance from the Sidoarjo Regency Government in a structured and coordinated manner.